Collusion-free public-key traitor tracing scheme - WANG Qing-long1; YANG Bo2; HAN Zhen1; GENG Xiu-hua1 (Tongxin xuebao)
All the existing traitor tracing schemes can trace at least a traitor when the number of traitors is not beyond a certain predefined value. However , how to prevent traitors from colluding a valid key is a open problem. A new traitor tracing scheme was presented, in which traitors can not get a valid key by conspiracy, no matter how many traitors there were because each user’s decryption key was independent of any others. Further, our scheme can determine a traitor in speediness and accuracy, thus it can reach a better determent to those potential bad users. Meanwhile, compared with present schemes, this scheme has a higher transmission efficiency.